The Effect of Local Product Challenges and Somethinc Product Innovation on Competitive Advantage with Technology Orientation as a Moderation - Fauziah; Muhammad Junaid Kamaruddin; Galuh Sukmaranti (MJK PUBLISHER, 2025)
This study aims to re-confirm whether there is an effect of product challenges and product innovation on competitive advantage moderated by technology orientation. And to determine the relationship between Technology Orientation motive in strengthening product challenge variables and product innovation. This study can provide Local Product Challenges that can be used as a reference for local beauty product entrepreneurs to know how to face competition by making superior products through technology-oriented product innovation. This study uses the structural equation modeling analysis method. The research design uses causality which aims to test the direct effect and moderating effect between variables. The software used is SmartPLS (Partial Least Square). Based on the results of the study, the Product Innovation Hypothesis Test and technology orientation significantly affect competitive advantage. . Based on the T-Statistic value of 3.608, and P Value of 0.000 and Coefficient Value of 0.328, it can be interpreted that these variables are interrelated and this Hypothesis is significant or accepted.